Current State of Soil Fertility Level of the Northern Forest Steppe of the Republic of Bashkortostan - Mindibayev, Radik A.; Ishbulatov, Marat G.; Safin, Khalil M.; Baikov, Aidar G.; Davletshin, Florid M. (Journal of Environmental Accounting and Management, 2026)
The research aims to study the dynamics of soil fertility of agricultural lands of the Northern forest-steppe. For this, in the process of field surveys, soil sections were laid, a description of the morphological structure with the selection of soil samples by genetic horizons. The field stage is carried out by route inspection, according to the coordinates of the previously designated points; sections are laid out with a description of all genetic horizons for the subsequent determination of the name of the soil. Based on the results of field, a digital soil map of agricultural lands was compiled.